PENGGUNAAN FLY ASH DAN BOTTOM ASH SEBAGAI CAMPURAN PEMBUATAN BATA RINGAN DENGAN MENGGUNAKAN PROSES CELLULAR LIGHTWEIGHT CONCRETE (CLC) - R., Bobby Asukmajaya R. (Universitas Islam Balitar Blitar, 2024)
FABA (Fly Ash and Bottom Ash) is a residual waste from burning coal which is widely used by industry to produce heat energy, an example is the use of FABA in PLTU (Steam Power Plant). One of the oldest PLTUs in Indonesia, namely PLTU PJB UP Paiton, has been using coal for a long time, the utilization of FABA is still quite minimal due to problems from the government in using FABA due to its entry into Hazardous and Toxic Material (B3) waste, but in 2021 through Regulation Government Number 22 of 2021 concerning the implementation of environmental protection and management is established if FABA is no longer included in B3 waste. The process of making lightweight bricks is divided into 2, namely AAC (Autoclaved Aerated Concrete) and CLC (Cellular Lightweight Concrete). because the process is relatively simple and does not require expensive special tools. In this study CLC was chosen because it seeks to improve the quality of small industrial materials, so that the products produced meet the standards set by the government. One way to use FABA waste is to make CLC lightweight brick mixture, because FABA material is classified as having a lighter specific gravity compared to the main material for making CLC fine aggregate at this time, namely sand. In this research, the effect of mixing FABA materials will be examined by substituting sand and cement, to obtain a mixture that is in accordance with SNI 8640: 2018 concerning Specifications for Lightweight Bricks for Wall Pairs. The results of the research show that the substitution of cement with fly ash produces a smaller dry specific gravity and an increase in strength in mixtures B and C, then the substitution of fine sand aggregate with bottom ash results in a reduction in the CLC specific gravity value, and the compressive strength increases in mixture E, F, G, and H. The CLC lightweight brick mixture that meets the individual and average compressive strength according to SNI 8640:2018 is mixture G.